Assessment of Self Disinfecting Capacity and Dimensional Stability of Irreversible Hydrocolloid Impression Material Mixed With Different Concentrations of Chlorhexidine Solution-An Invitro Study - Pradhan, B.; Joshi, S. P.; Sah, S.; Verma, A. (Journal of Nepalese Prosthodontic Society, 2021)
Introduction: Impression materials are used to record the anatomical topography of oral tissues. Irreversible hydrocolloid is an impression material routinely used in dentistry. However, it retains bacteria, 2 to 3 times higher than other impression material. Spraying and immersion technique has been employed for disinfection of irreversible hydrocolloid with varying degree of success. Thus the need of impression material that has self-disinfecting capacity seems to be very important to have infection control in dentistry.Materials and Methods: This invitro study was done in two parts. Assessment of self-disinfecting capacity of irreversible hydrocolloid impression material mixed with different concentrations of chlorhexidine solution and dimensional stability of irreversible hydrocolloid impression material mixed with different concentrations of chlorhexidine solution. For assessment of self-disinfecting capacity, irreversible hydrocolloid was mixed with various concentrations of chlorhexidine (0.05%, 0.1%, 0.2%) and distilled water. Total 64 culture plates were prepared, n=16 for each group of microorganisms (E. coli, S. aureus, Pseudomonas, Klebsiella). Inhibition zones were measured for each microorganism. For dimensional stability, the specimens were divided into four groups similar to specimen for self-disinfecting ability. Total 56 samples were prepared, n=14 for each group. Interpretation (IP), Mesiodistal (MD), Buccolingual (BL), Occlusogingival (OG) dimensions were measured by digital Vernier caliper. One-way analysis of variance was done for assessment of self-disinfecting capacity and for dimensional stability. Dunnett comparison test was performed to test the significance between test and control. P value was calculated under the predetermined level of significance (0.05).Results: Zones of inhibition were observed around test specimens (groups 0.05, 0.1, 0.2), but not around control specimen (Group d/w). There was a significant difference in the mean diameters of the inhibition zones between test groups and control which was statistically highly significant (p < 0.001). In the test for dimensional stability, no significant differences were detected among groups for all the measured dimensions (p> 0.05).Conclusion: Irreversible hydrocolloid impression material mixed with chlorhexidine exhibits varying degrees of self-disinfecting activity without influencing the dimensional stability of set material.